Smart Cities - Conditions for Creating New Quality of Life for Population - DANILOV, Oleg F.; GUSAROVA, Miroslava S.; OSIPENKO, Aleksey M.; SMOLENTSEV, Vasiliy. M. (Journal of Environmental Management and Tourism; Vol 9 No 4 (2018): JEMT Volume IX Issue 4(28) Summer 2018, 2018)
The sustainable development of cities makes them viable, adaptable, to mitigate adverse impacts, to stimulate positive socio-economic and environmental changes. The main goal of the work is to explore smart cities, which contribute to a new quality of life for the population. The authors described the main elements of such cities, the relationship between quality of life and satisfaction, analyzed the factors that contribute to the quality of life. It is established that roads, transport, social programs, modern education, adaptive ecology and others influence the quality of life in the cities studied. It is revealed that the quality of life determines the effectiveness of people's way of life. The level and conditions of life are the structural components of the quality of life. As a result, it can be concluded that the standard of living depends on material, spiritual, social needs, which are related to social society, empathy, help from other people.